Steel women. Spanish communists and the Women’s International Democratic Federation (1945-1950) - Yusta Rodrigo, Mercedes (Hispania Nova, 2020)
The article addresses a little-known facet of the history of the militancy of Spanish communist women in exile : their participation in an international organization, the Women’s International Democratic Federation, created in Paris in 1945 with the aim of federating anti-fascist women’s organizations worldwide. The Spanish communists, led by Dolores Ibárruri, played a very important role in defining the strategies and organization of the Federation itself, which represents a very important case of transnational women’s mobilization in the context of the Cold War. The article discusses the creation of women’s anti-fascist organizations in the long term, describes the role of the Spanish communists within the FDIM, and finally analyzes the relationship between the FDIM and the anti-Franco mobilization, which includes the creation of a common political language within this women’s movement, very marked by political motherhood.